The traditional assessment affects the english learning process in the seventh grade of students at cenaculo school academic year 2011 – 2012 - Martínez Molina, Hirlanda Belén (2013)
This project analyzes the reasons why Traditional Assessment affects the English learning process of students from seventh grade group A at Unidad Educativa Padres Somascos El Cenaculo that emerges from the necessity to improve the English language acquisition, the student’s performances, and his learning process. In order to collect data and be able to give a right diagnostic, it was necessary to apply a survey and a test to thirty six students from 7th grade group A; one survey to thirty six parents, and another survey was conducted to seven English teachers. An interview was applied to the Principal, to the English coordinator and to the English teacher from that course also class observations were made too……